2015
DOI: 10.2310/8000.2013.131314
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alternative diagnoses in patients with suspected uncomplicated renal colic undergoing computed tomography: a prospective study

Abstract: Objectives: Unenhanced computed tomography (CT) has become a standard imaging technique for uncomplicated renal colic in many countries. The appropriate timing of CT imaging has not been established, and guidelines recommend that this imaging be performed between 1 and 7 days of presentation. The primary objective of this study was to determine the prevalence of alternative diagnosis identified with low-dose unenhanced CT in the emergency department (ED) in patients with suspected uncomplicated renal colic. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Poletti et al reported the same detection rate of alternative diagnosis in their series, 8 but it is more common that LDCT reports lower rates of detection for alternative diagnosis. 7–9 , 14 , 15 Nonetheless, imaging to evaluate nephrolithiasis does not require evaluation of alternate soft tissue diagnoses, for example, the use of KUB X-rays for renal stones.…”
Section: Discussionmentioning
confidence: 99%
“…Poletti et al reported the same detection rate of alternative diagnosis in their series, 8 but it is more common that LDCT reports lower rates of detection for alternative diagnosis. 7–9 , 14 , 15 Nonetheless, imaging to evaluate nephrolithiasis does not require evaluation of alternate soft tissue diagnoses, for example, the use of KUB X-rays for renal stones.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with most of the existing guidelines, [9][10][11][12][13] probably because CT can eliminate most of the alternative diagnoses and shows better diagnostic performances. [17] However, in a recent large multicentre randomized trial, Smith-Bindman et al found that initial ultrasonography for suspected renal colic was associated with lower cumulative radiation exposure than initial CT without significant differences in missing high-risk diagnoses, which emphasizes that controversies regarding this question are still ongoing. [18] Analgesics…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…However, most hospitals do not have this technology, which in addition has very limited usefulness in case of ureteral stones. CT can identify the presence and size of stones with a very high accuracy of >95 % and is able to detect alternative diagnoses that simulate renal colic in 5–10 % of patients [ 16 , 17 ]. Nonetheless, in spite of its high accuracy, there is increasing concern about the increase of health care costs and radiation risk that accompanies CT scans, since the use of CT rarely changes the treatment plans of these patients [ 18 ].…”
Section: When To Use Imaging In Renal Colicmentioning
confidence: 99%